PRIMARY DIAGNOSIS OF PSYCHO-EMOTIONAL STATES OF ATHLETES OF THE RUSSIAN WHEELCHAIR CURLING TEAM - Dikhor, V.A.; Batugin, A.A.; Burkova, A.M.; Shamo, S.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to conduct a primary psychological diagnosis of athletes of the main team of the Russian wheelchair curling team. Methods and structure of the study. Eight athletes of the main composition of the Russian national team aged 33 to 52 years old took part in the scientific work: four men and four women. For diagnosis, four basic methods for diagnosing indicators of stress and anxiety were chosen: a method for diagnosing self-esteem Ch.D. Spielberger, Yu.L. Khanina (assessment of situational and personal anxiety); inventory of stress symptoms (T. Ivanchenko et al.); scale for assessing subjective comfort (A. Leonova); diagnostics of the state of stress (K. Schreiner). Results and conclusions. According to the results of the diagnostics, it was revealed that the athletes of the main team of the Russian national team are able to get together and respond constructively in a tense situation, but at the same time they are prone to anxiety, which can cause errors during the competition. Based on the data obtained, a sports psychologist developed a correctional program aimed at reducing the levels of situational and personal anxiety, as well as the formation of skills for conscious self-regulation and emotional relaxation.